High serum unconjugated bilirubin levels following successful treatment of antiepileptic drug-induced bullosa epidermolysis: a case report and review of the literature - Cheng, Chen; Sun, Yangyang; Zhang, Bingfeng; Xu, Huaguo; Xu, Jian; Zhang, Jiexin (Frontiers in Medicine, 2025)
Most of the classical antiepileptic drugs (AEDs) such as lamotrigine (LTG) and levetiracetam (LEV) are known to potentially cause skin lesions and liver injury. This paper reports an unusual phenomenon that serum levels of unconjugated bilirubin (IBIL) abnormally increased after the successful treatment of AED-induced bullosa epidermolysis, regardless of the presence of genetic mutations associated with hepatocellular bilirubin metabolism. A 14-year-old female, who was suffering from epilepsy, presented to our hospital with fever and red papules all over her body. Based on histopathological examination of the skin biopsy specimen and a medical history of LTG and LEV use, toxic epidermal necrolysis (TEN) was confirmed. After methylprednisolone treatment for 29 days, the skin lesions showed retreated but drug-induced liver injury (DILI) aggravated. Serum biochemical test results revealed elevated levels of serum total bilirubin, conjugated bilirubin, IBIL, gamma glutamyl transpeptidase, alkaline phosphatase, total cholesterol, and total bile acid. B-ultrasound examination indicated cholecystitis. The upper abdominal magnetic resonance cholangiopancreatography was performed four times on her and revealed progressive dilatation of the biliary ducts and cholestasis. A whole-exon sequencing of the liver biopsy specimen revealed a heterozygous 1249G>A mutation in the ATP binding cassette subfamily C member 2 gene and a heterozygous 211G>A mutation in the UDP glucuronosyltransferase family 1 member A1 gene. Hepatobiliary protection regimen was administered for a total of 71 days to reduce serum bilirubin level and to relieve symptoms. Nevertheless, the patient developed chronic DILI. The serum IBIL levels showed limited response to the regimen and instead increased to as high as 344.6 μmol/L. After taking phenobarbital, the IBIL level decreased only to 270.2 μmol/L. However, we documented a strong inverse correlation between serum creatine kinase (CK) and IBIL levels, which has not been discussed in other reported cases of AED-induced liver injury. This case emphasizes that the precise interpretation of serum hepatobiliary indexes is important for differentiating energy imbalance from organic integrity. A combination of serum CK and IBIL may serve as a useful laboratory tool for DILI stage assessment.